IMPLEMENTASI MANAJEMEN PENDIDIKAN ISLAM DALAM PEMBENTUKAN KARAKTERISTIK ISLAM ANAK MIGRAN DI MUAR JOHOR MALAYSIA - Adnan Buyung Nasution; Surono ZR; Zaitun Husseina Nasution; Siti Nursyah Fitri; Dwi Raisyah (Smart Education, 2025)
Abstract: This study aims to analyze the implementation of Islamic educational management in shaping the Islamic character of migrant children in Muar, Johor, Malaysia. Migrant children face various challenges, including lack of legal doc- uments, limited access to formal education, and the risk of losing their Islamic identity due to the influence of a new environment. This research employed a qualitative descriptive method conducted at an Islamic educational institution ac- commodating 24 migrant students. The findings reveal that the functions of Islam- ic educational management planning, organizing, actuating, and controlling were consistently implemented despite limited resources. Islamic habituation programs, talent-based guidance, structured learning, and supervision of worship discipline became the school’s main strategies. These efforts successfully fostered Islamic character among migrant children, reflected in their discipline in worship, sense of responsibility, politeness, self-confidence, and teamwork. Thus, Islamic educa- tional management plays a significant role in strengthening Islamic identity and building positive character among migrant children, providing an educational solution amid legal and facility constraints.Keywords: Islamic educational management, character education, migrant chil- dren, Muar Johor. Abstrak: Penelitian ini bertujuan untuk menganalisis implementasi manajemen pendidikan Islam dalam pembentukan karakteristik Islam anak migran di Muar, Johor, Malaysia. Anak-anak migran menghadapi berbagai problematika, mulai dari keterbatasan dokumen resmi, akses terbatas terhadap pendidikan formal, hingga risiko kehilangan identitas keislaman akibat pengaruh lingkungan baru. Penelitian menggunakan metode kualitatif dengan pendekatan deskriptif, dil- akukan di salah satu lembaga pendidikan Islam yang menampung 24 peserta didik anak migran.Hasil penelitian menunjukkan bahwa fungsi-fungsi manajemen pen- didikan Islam perencanaan, pengorganisasian, pelaksanaan, dan pengawasan telah dijalankan secara konsisten meskipun dalam keterbatasan. Program pembiasaan Islami, pembimbingan sesuai potensi, pembelajaran yang terarah, sertapengawasan kedisiplinan ibadah menjadi strategi utama sekolah. Implementasi tersebut berhasil membentuk karakter Islami anak-anak migran, yang tercermin dalam disiplin ibadah, tanggung jawab, sopan santun, kepercayaan diri, serta sikap kebersamaan. Dengan demikian, manajemen pendidikan Islam terbukti berperan penting dalam memperkuat identitas keislaman dan membangun karakter positif anak migran, sekaligus menjadi solusi pendidikan di tengah keterbatasan legalitas dan fasilitas. Keywords: manajemen pendidikan Islam, pendidikan karakter, anak migran, Muar Johor.